New Forms of Volunteerism in Public Health. Professionalization Processes in Complementary and Alternative Medicine Field - Saizar, María Mercedes (2017)
Based on a phenomenological and qualitative approach the paper will focus on the emergence anddefinitions of roles of a new type of social volunteers in the public health system of Argentina. The relevance ofthis election is based on the differential traits this way of participation has as against other modes of insertionin the health sector that existed in different historical periods; that is to say, the differences between old andnew volunteers. In this framework, we will emphasize our analysis in how these new ways of volunteerism shapea series of strategies of inclusion of complementary and alternative medicines in the public healthcare system,introducing in an unofficial manner discourses and practices for healthcare different to those proposed byofficial biomedicine